Knowledge and attitude of pregnant women about preeclampsia in King Abdulaziz Medical City, Western Region: A cross-sectional study - Fatimah Ahmed Alsabi; Abeer Mokhtar Orabi; Eman Zain Bajamal (PLoS ONE, 2025)
Introduction Preeclampsia is a serious obstetrics condition generally diagnosed by the presence of high blood pressure (≥140/90 mmHg) and significant protein in urine (≥ 2++ on dipstick urine test) developing for the first time after 20 weeks of pregnancy. It poses severe risks to both mother and newborn, including the potential for maternal and neonatal mortality and morbidity. Although preeclampsia is a well-recognized pregnancy-related complication, there is a notable lack of knowledge and awareness among pregnant women in Saudi Arabia, particularly concerning its signs, symptoms, risk factors, and the importance of timely medical intervention. This study aims to assess the level of knowledge and attitude regarding preeclampsia among pregnant women attending King Abdulaziz Medical City in Jeddah, Saudi Arabia. Methods In this quantitative cross-sectional study, 122 pregnant women visiting the Obstetrics and Gynecology Outpatient Department were surveyed from April to June 2023. The research employed a structured questionnaire to collect detailed information on participants’ sociodemographic backgrounds, knowledge about preeclampsia symptoms, risk factors, complications, and attitudes toward its prevention and the recognition of danger signs. Data were analyzed using descriptive statistics as well as ANOVA test, T-test, and Pearson correlation to explore relationships and significance among study variables. Results The study revealed an average knowledge score of 25.43 (SD = 5.67), indicating that many participants demonstrated a moderate understanding of preeclampsia. On the other hand, the attitude score averaged 23.39 (SD = 3.11), showing that participants held favorable attitudes toward the risk factors, prevention, and complications of preeclampsia. Notably, participants with higher education levels and those who were employed demonstrated higher knowledge scores. Conclusion The findings reflect a moderate level of understanding among participants but also highlight critical areas where knowledge enhancement is necessary to enable timely intervention and reduce adverse maternal and neonatal outcomes.